2005
DOI: 10.1300/j125v13n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Community Centers in Urban China

Abstract: While China's economic progress and social transformation demand an urgent refurbishment of its social welfare system, after a decade of development community centers have gradually become the major infrastructure of service delivery in urban China. In this article, the authors examine the social and historical context of the development of community services in urban China, and then focus on the community center as an emerging force in a society undergoing considerable change. A study of community centers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…For nonmedical services, Xu et al (2005) found that services provided at community centers varied greatly in terms of quality and quantity, and generally there was no financial support from the government. Sufficient financial support coupled with a well-trained staff could improve the quality and availability of CBSS.…”
Section: Discussionmentioning
confidence: 99%
“…For nonmedical services, Xu et al (2005) found that services provided at community centers varied greatly in terms of quality and quantity, and generally there was no financial support from the government. Sufficient financial support coupled with a well-trained staff could improve the quality and availability of CBSS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, filial piety in China and similar norms and values in other cultures provide social and emotional support to older persons. At the village level, some villages have established "community centers" that offer social activities for older adults (Xu, et al, 2005). These social supports have become increasingly important with the changing dynamics of the Chinese family and its struggle to support the elderly.…”
Section: Social Characteristicsmentioning
confidence: 99%
“…The elected resident committee, as a major decision‐making body in the community, holds regular meetings. The function of community service delivery was reorganized into a community service center staffed by professional social workers (Xu, Gao, and Yan 2005). The elected resident committees select competent staff into the community service center and oversee and evaluate their performance.…”
Section: A Top‐down Approach In Shanghaimentioning
confidence: 99%